Enhancing Waste Management Practice - The Appropriate Strategy for Improving Solid Waste Management System in Vietnam Towards Sustainability - Song Toan Pham Phu; Yen Anh Tran Thi; Giang Minh Hoang; Cuong Dinh Le; Takeshi Fujiwara; Dinh Van Pham; Hoa Kieu Thi (Chemical Engineering Transactions, 2020)
This study aims to build the appropriate model of waste management practice (WMP) towards sustainable municipal solid waste (MSW) system in a city of developing country like Vietnam. A waste audit was performed and material flow analysis method was simulated to describe and analyse the current status of MSW system and its assumpted models. Four WMP models were built based on the feature of the region, the intention and optimisation of WMP, and the consensus of the government. This study shows that the improvement of the SWM system can reduce a significant amount of waste to landfill. Notably, the waste reduction performance is 5.0, 7.8, 11.11 and 29.3 % in S1, S2, S3 and S4, respectively. Also, the recovery performance of recyclables changes in proportional to the level of SWM practice and reach at 3.78, 5.843, 4.593, and 7.120 t/d, respectively. This study reveals that the improvement of SWM practice at source from intentional to optimal rate is the sustainable strategy for developing an SWM system in Hoi An City.